G (x) = (x + 8) / 3'ün tersi nedir?

G (x) = (x + 8) / 3'ün tersi nedir?
Anonim

Cevap:

# g ^ -1 (x) = 3x - 8 #

Açıklama:

let #y = g (x) #. Yani, #y = (x + 8) / 3 #

# 3y = x + 8 #

#x = 3y - 8 #

# g ^ -1 (y) = 3y - 8 #.

Bu nedenle, # g ^ -1 (x) = 3x - 8 #

İstesek, önce bunu ispatlayabilirdik. # G # herhangi biri için göstererek # X_1, x_2inA #, nerede # A # etki alanı # G #, #g (x_1) = gr (x_2) #

# x_1 = x_2 #, yani # x_1 + 8 = x_2 + 8 # ve # (x_1 + 8) / 3 = (x_2 + 8) / 3 #

Eğer tutarsa # x_1 = x_2 #, #g (x_1) = g (x_2) #.

Böylece, # G # ters çevrilebilir.